Energy and Economic Analysis of Tropical Building Envelope Material in Compliance with Thailands Building Energy Code - Pathomthat Chiradeja; Atthapol Ngaopitakkul (My University, 2019)
The building envelope has a direct impact on the overall energy consumption of a building. Thus, an improvement in the building envelope using energy-efficient material can yield the desired energy performance. This study is based on the materials and compositions used in building envelopes in compliance with the building energy code of Thailand. The building under study is an educational building located in Bangkok, Thailand. Both the energy and the economic aspects of retrofitted building envelopes are discussed in this study. The energy performance was evaluated by calculating the thermal transfer value and whole building energy consumption using the building energy code (BEC) software. The simulation was done under the assumption that the building envelope in the case study building was retrofitted with different materials and compositions. The study determines the feasibility of retrofitting buildings using energy-efficient material by utilizing the discounted payback period and internal rate of return (IRR) as indicators. The results show that retrofitted building envelopes in every case can reduce the whole building energy consumption. In the best envelope configuration, energy consumption can decrease by 65%. In addition, the economic potential is also high, with an IRR value of approximately 15% and a payback period of 23 less than nine years. These finding indicate that a building envelope made with energy-efficient material can achieve good results for both energy performance and economic feasibility.
Keywords: Payback period; Building envelope; Building code; Retrofitting; Envelope (radar); Building material; Embodied Energy; Energy accounting; Building Energy and Comfort Optimization